The african leaf extract (Vernonia amygdalina): analgesic effect as cyclooxygenase enzyme inhibitor: Ekstrak daun afrika (Vernonia amygdalina): efek analgesik sebagai inhibitor enzim siklooksigenase - Amalia I; Lenni Indriani; Nurul Inayah Haspullah; Nurwahyuni (Makassar Dental Journal PDGI Makassar, 2023)
Pain is an unpleasant experience that can be a sensory experience that includes time, space and emotions that can be experi-rienced by every individual. One of the drugs used as an analgesic is paracetamol which is non-steroid anti-inflammatory drugs (NSAID) class of drugs. Afrikan leaves (Vernonia amygdalina) were found to have an analgesic effect or relieve pain due to the presence of flavonoids, tannins and saponins. It can be concluded that the bioactive compounds contained in african leaf ex-tract have an analgesic effect. The analgesic effect is obtained from flavonoids which have activity similar to paracetamol, namely inhibiting the formation of inflammatory mediators through inhibition of the cyclooxygenase enzyme.